Analisis Perbuatan Melawan Hukum Terhadap Obyek Sengketa Tanah Yang Dikuasai Orang Lain (Studi Putusan Nomor : 2490 K/Pdt/2015) - Septesha, Widya Ade; Badriyah, Siti Malikhatun (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
This research aims to find out what the status of land ownership is according to the Basic Agrarian Law and how land disputes resulting from unlawful acts are resolved in terms of UUPA No. 5 of 1960, which using normative legal research methods concluded that: 1. Land ownership status is an important thing , because it concerns someone's ownership, we all know that land ownership is an important thing in human life, where we live on land, so land ownership status is really needed by everyone. Ownership of a certificate is evidence that has clear legal force. The Basic Agrarian Law is the basic rule that regulates land in Indonesia. With the development of the times, new rules have been born, either contained in law or government regulations, which have been designed in such a way as to meet needs and have succeeded in perfecting the rules regarding land ownership status. which can be carried out by the Indonesian people. 2. Regarding dispute resolution, it does not have to be resolved in court, but rather deliberation or family or local government to resolve the dispute so that it does not end up in court and becomes a big problem. A dispute occurs, causing many parties to take legal action, even though there is another way, namely by deliberation to reach a consensus, which fails, so they usually take the matter to the sub-district or to the land office, in this case to the village or the head of the Land Office who helps resolve it. In this case they only act as mediators or are often called mediators.